Impact of Social Protection Programme through VDBs in alleviates Rural Poverty in Nagaland: A Macroeconomic Approach - Jamir, Chubakumzuk; Moameren Pongen (Garuda Prestasi Nusantara Consulting, 2024)
Understanding the relationship between macroeconomic policies and rural poverty still remains a key policy challenge. This study builds a fundamental framework to connect important macroeconomic factors with rural poverty and evaluates the impact of government-led development expenditure policies that have had a direct impact on rural poverty during the past two decades. In order to ensure inclusive growth in the social protection programme, it is necessary to address the needs and ambitions of this disadvantaged section of population. Employing the data produced from household surveys, National Sample Survey Organization, Statistical Handbook, carried out a social protection programme through descriptive statistics and linear regression model. The results show that the prevalence of poverty in rural sector has significantly decreased from 10% in 2004-05 to 6.10% in 2011-12 but shows positive increase in 2021-22 to 12.75%. Therefore, the government must implement effectively the social protection programme so that the there will be increase the level of income and thus help in reducing income inequality. Also, suggested that proper physical and social overhead capital i.e., infrastructure need to developed and priority be given in the rural sector.